SYDNEY CARTON AS A SUBJECT AND OBJECT IN A TALE OF TWO CITIES NOVEL - Mulyadi, Randy (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2018)
The article entitled â€œSydney Carton characterâ€™s as a Subject and Object in A Tale of Two Cities novelâ€ analyzes a character named Sydney Carton who has important role in a story who is becoming subject and object during events in a story and they occur in the same time. This research uses narratology by Mieke Bal (2009) and focused on subject and object in actors element of element of fabula. This research is purposed to analyze Cartonâ€™s role for other characters in the story. To analyze those issues, qualitative method and descriptive analysis are used. This research shows that Cartonâ€™s position is significant when he plays the role. This research is significant because Carton has double position in one moment, as a subject that oppress object and as an object that oppressed by the subject.